2014
DOI: 10.1371/journal.pone.0100635
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Chemical Dynamic Approach to Correlate Autoimmunity and Optimal Vitamin-D Range

Abstract: Motivated by several recent experimental observations that vitamin-D could interact with antigen presenting cells (APCs) and T-lymphocyte cells (T-cells) to promote and to regulate different stages of immune response, we developed a coarse grained but general kinetic model in an attempt to capture the role of vitamin-D in immunomodulatory responses. Our kinetic model, developed using the ideas of chemical network theory, leads to a system of nine coupled equations that we solve both by direct and by stochastic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…A recent study evaluating the effects of vitamin D in immune modulation showed a direct correlation of vitamin D levels with T regulatory cells and an inverse correlation with T effector cells, which are both related in the pathogenesis of autoimmune diseases. These authors suggested that there is an optimal vitamin D level to control immune regulation and pathogenic resistance ( 35 ). Clinical studies also suggested a U-shaped relation between vitamin D levels and different disorders so that both low and high levels were associated with the diseases ( 36 , 37 , 38 , 39 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating the effects of vitamin D in immune modulation showed a direct correlation of vitamin D levels with T regulatory cells and an inverse correlation with T effector cells, which are both related in the pathogenesis of autoimmune diseases. These authors suggested that there is an optimal vitamin D level to control immune regulation and pathogenic resistance ( 35 ). Clinical studies also suggested a U-shaped relation between vitamin D levels and different disorders so that both low and high levels were associated with the diseases ( 36 , 37 , 38 , 39 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that quercetin enhances the immediate bioavailability of RV (RV makes more passes through the liver before complete metabolization). Vitamin D 3 controls a variety of genes involved in innate immunity, inflammation, and vascular calcification and has recently emerged as an important nutrient (prohormone) against AMD [ 12 , 13 ]. IP6 (inositol hexaphosphate) from rice bran is nature’s divalent mineral binder ( i .…”
Section: Methodsmentioning
confidence: 99%
“…However, those who believe in a role for vitamin D beyond calcium and bone health, suggest that these levels do not apply to global health and higher cut-offs for sufficiency should be used (4). For example, to observe immune effects, levels well above 100 nmol/L need to be achieved (5). Here, we discuss two different viewpoints on screening for vitamin D status: for and against.…”
Section: Introductionmentioning
confidence: 98%